Studies on Early Germination of Gum Arabic (Acacia senegal) Tree Species Using Different Water Qualities - R, Umar M.; K, Delanice S.; S, Bode A. (African Multidisciplinary Journal of Sciences and Artificial Intelligence, 2025)
This study was carried out to access different water qualities on germination of Acacia senegal seeds in other to determine conditions that promote successful germination. Water quality use was (Borehole, River and Well water). Laboratory analysis on water quality was conducted. Different parameters on growth of Acacia senegal species (height, stem diameter and number of leaves) using borehole, well and river water. Results shows that stem diameter of river water recorded the highest value of (2.38m) while borehole and well water having values of (2.09m) and (0.43m) respectively. The height of river water recorded the highest value (30.08m) in parameters of Acacia species while lowest values was found in borehole and well water (28.31m) and (28.81m). Number of leaves gave the highest value of (184.93) and lowest in borehole and well water with values (142.6) and (158.0). All parameters measured highest in week 8 while lowest in week 1. Water quality test also reveals that Cl, Mg and Na show low results in the quality test for water. The result for the water quality test for pH, EC, Ca, Mg, Na, CO3, HCO3 and Cl showed no significant (p<0.05) between the pH of the borehole, well and river (6.66, 6.31 and 6.23) respectively also Cl recorded highest in well water 21.63, lowest in borehole and river water 19.25 both. Correlation analysis reveals strong positive linear relationships in stem, height and number of leaves in the different types of water (river, well and borehole) with values (0.996, 0.994 and 0.995) respectively. It is concluded that that river water boosts the germination rates of Acacia senegal seeds due salinity content in the study area. Further research can be geared toward using different water quality in determination of the growth parameter for different tree species.